Etika Persaingan Dalam Usaha Menurut Pandangan Islam - Abdul Latif (Islamic Economics Journal, 2017)
Islamic Business Ethics is an important thing in the journey of professional business activity, and shows. There is an independent structure that is separate from other structures. because business ethics in Islam mostly explains the policy and truth both the level of intention and the idea of  behavior, Islam to trade relations. Trading in Islam is now beginning to show its fangs. This is due to the collapse of the capitalist economy due to the global crisis. And in everyday life a person will never be separated from economic activities, especially Islamic economics In practice, Islam recommends that based on Islamic law of Qur’an and sunnah.